Pengakuan, Pengukuran, Penyajian, Dan Pengungkapan Aset Kelolaan Pada Lembaga Amil Zakat - Ghufraanaka Ghufraanaka; Dina Fitrisia Septiarini (Jurnal Ekonomi Syariah Teori dan Terapan, 2016)
The purpose of this research is to assess the implementation of accounting aspects such as recognition, measurement, presentation and revelation of zakat transactions within LAZISMU in regards to PSAK 109 concerning zakat accounting. This research employs a qualitative descriptive approach with case study methodology. The technique of analysis used within this research is the domain analysis technique. The research determines two domains in relation to zakat accounting, which are acquisition, management and distribution of zakat, infaq and shadaqah. Results suggest that in the aspect of recognition and measurement, LAZISMU demonstrated compliance to the PSAK 109 during the acquisition of zakat, infaq and shadaqah, however LAZISMU failed to show compliance in regard to the aspects of revelation and presentation during the acquisition process. In conclusion, LAZISMU are not compliant to the general guide of zakat accounting, mostly due to lack of able personnel in LAZISMU.